Risk factors for severe adult-onset asthma: a multi-factor approach - Toppila-Salmi, Sanna; Lemmetyinen, Riikka; Chanoine, Sebastien; Karjalainen, Jussi; Pekkanen, Juha; Bousquet, Jean; Siroux, Valérie (BMC pulmonary medicine, 2021)
Background The aim was to identify risk factors for severe adult-onset asthma. Methods We used data from a population-based sample (Adult Asthma in Finland) of 1350 patients with adult-onset asthma (age range 31–93 years) from Finnish national registers. Severe asthma was defined as self-reported severe asthma and asthma symptoms causing much harm and regular impairment and ≥ 1 oral corticosteroid course/year or regular oral corticosteroids or waking up in the night due to asthma symptoms/wheezing ≥ a few times/month. Sixteen covariates covering several domains (personal characteristics, education, lifestyle, early-life factors, asthma characteristics and multiple morbidities) were selected based on the literature and were studied in association with severe asthma using logistic regressions. Results The study population included 100 (7.4%) individuals with severe asthma. In a univariate analysis, severe asthma was associated with male sex, age, a low education level, no professional training, ever smoking, ≥ 2 siblings, ≥ 1 chronic comorbidity and non-steroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (NERD) (p < 0.05), and trends for association (p < 0.2) were observed for severe childhood infection, the presence of chronic rhinosinusitis with nasal polyps, and being the 1st child. The 10 variables (being a 1st child was removed due to multicollinearity) were thus entered in a multivariate regression model, and severe asthma was significantly associated with male sex (OR [95% CI] = 1.96 [1.16–3.30]), ever smoking (1.98 [1.11–3.52]), chronic comorbidities (2.68 [1.35–5.31]), NERD (3.29 [1.75–6.19]), and ≥ 2 siblings (2.51 [1.17–5.41]). There was a dose–response effect of the total sum of these five factors on severe asthma (OR [95% CI] = 2.30 [1.81–2.93] for each one-unit increase in the score). Conclusions Male sex, smoking, NERD, comorbidities, and ≥ 2 siblings were independent risk factors for self-reported severe asthma. The effects of these factors seem to be cumulative; each additional risk factor gradually increases the risk of severe asthma.